Unusual Biliary Complication following Christmas Eve Dinner - Kunovsky, Lumir; Tesarikova, Pavla; Sethi, Amrita; Kroupa, Radek; Dastych, Milan; Dolina, Jiri; Kala, Zdenek; Trna, Jan (Digestive diseases (Basel, Switzerland), 2021)
We present a case of a fish bone impacted in the papilla of Vater resulting in dyspepsia and mild elevation in liver function tests, which was subsequently treated endoscopically. Fish bones are one of the most commonly encountered swallowed foreign bodies. However, involvement of the biliary tract, such as the one described by us, represents an extremely rare complication of fish bone ingestion. The diagnosis of a foreign body in the biliary tract can be difficult, and early endoscopic or surgical extraction may be required to avoid complications such as biliary stone formation, obstructive jaundice, cholangitis or cholecystitis, and/or biliary sepsis. Prompt endoscopic treatment can avoid severe biliary complications or surgical therapy.
Keywords: cholangitida; Biliary Tract; Biliary complications; Endoscopy; Fish bone; Gallstones; jídla; Cholangiopancreatography, Endoscopic Retrograde; Cholangitis; Humans; žlučové ústrojí; Papilla of Vater; Foreign body; žlučové kameny; Common bile duct; lidé; Meals; cholangiopankreatografie endoskopická retrográdní